Biodiversity and geography - Michael Rauscher; Edward B. Barbier (Universität Rostock, Institut für Volkswirtschaftslehre, 2007)
The paper combines an economic-geography model of agglomeration and periphery with a model of species diversity and looks at optimal policies of biodiversity conservation. The subject of the paper is 'natural' biodiversity, which is inevitably impaired by anthropogenic impact. Thus, the economic and the ecological system compete for space and the question arises as to how this conflict should be resolved. The decisive parameters of the model are related to biological diversity (endemism vs. redundancy of species) and the patterns of economic geography (centrifugal and centripetal forces). As regards the choice of environmental-policy instruments, it is shown that Pigouvian taxes do not always establish the optimal allocation.
Keywords: Q56; Q57; Q58; R12; R14; R23; 330; biodiversity; new economic geography; agglomeration; species redundancy vs. endemism; environmental regulation; Biodiversität; Neue ökonomische Geographie; Regionale Konzentration; Naturschutz; Umweltpolitik; Umweltö